Dense discrete phase model for tumor cell growth analysis in fluid environments - Urdeitx Diaz, Pau; Hidalgo, Victor; Doweidar, Mohamed H. (Jornada de Jóvenes Investigadores del I3A, 2022)
Cell-cell and cell-extracellular matrix interactions play a major role in tumor growth, which involves complex molecular intercommunications. We have developed a single-cell computational model in which fluid dynamics and cell-cell interaction are coupled to evaluate the growth of cancer cells in fluidic environments. The results demonstrate that, once the cell concentration increases, the cell-cell interaction increases, decreasing cell maturation time and increasing tumor growth rate.